The Correlation Between Land Ownership Status, Parents Occupation, and Future of Agriculture with the Youth Attitude who Work in Agricultural Sector (Case of Pamijahan Sub-District, Bogor District) - Nugraha, Yogaprasta Adi; Martha, Layung Paramesti (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2020)
The objectives of this research were (1) identifying parents’ land ownership status in Pamijahan Sub-District, Bogor District, (2) Identifying parents’ occupation in Pamijahan Sub-District, Bogor District, (3) Identifying the youth preference towards residency place in the future, (4) analyzing the correlation between land ownership status, parents’ occupation, youth future residency preference and rural-youth attitude towards agricultural sector. This research was performed in Ciasmara Village, Pamijahan Sub-District, Bogor District, from 2019 to 2020, using quantitative method and chi-square to identify the association between land ownership status, parents’ occupation, youth future residency preference, and rural-youth attitude towards agricultural sector. This research found that parents’ occupation and youth future preference towards residency place were correlated with rural-youth attitude towards agricultural sector